Development of the Malocclusion Impact Questionnaire (MIQ) to measure the oral health-related quality of life of young people with malocclusion: part 1 – qualitative inquiry - Patel, Neil (J Orthod, 2016)
Objectives: To seek the views of adolescents with malocclusion about how the appearance and arrangement of their teeth affects their everyday life and to incorporate these views into a new Malocclusion Impact Questionnaire (MIQ). Methods: Semi-structured interviews were undertaken with a purposive sample of 30 young people (10–16 years) referred for orthodontic treatment to two dental teaching hospitals. The interviews were recorded, transcribed and analysed using framework analysis. Several themes and sub themes were identified and these were used to identify items to include in the new measure. Results: Three themes emerged which were: concerns about the appearance of their teeth, effect on social interactions and oral health/function. Participants expressed the view that their teeth did not look normal, causing them embarrassment and a lack of confidence, particularly when they were with their peers or having their photograph taken. Concerns regarding the potential effect of a malocclusion on oral health, in terms of food becoming stuck between crooked teeth, interferences when chewing and increased risk of damaging the teeth were also identified. The themes were used to generate individual items for inclusion in the questionnaire. Conclusions: Common themes relating to the impact of malocclusion on the lives of young people were identified and generated items for the new MIQ to measure the oral health-related quality of life of young people with malocclusion. Part 2 outlines the further development and testing of the MIQ.